Biodiversity of maize on farms in Kenya - Smale, Melinda; de Groote, Hugo; Owuor, George (International Food Policy Research Institute, 2006)
In recognition of the importance of genetic resources, international agreements, such as the Convention on Biological Diversity (CBD) and the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA), encourage national governments to support the sustainable use and management of genetic resources on farms and in gene bank collections. To design initiatives to support the local management of crop biological diversity in farming communities, an understanding of the social and economic factors that determine the observed levels is needed.